Clonotypic Analysis of Immunoglobulin Heavy Chain Sequences in Patients with Waldenström's Macroglobulinemia: Correlation with MYD88 L265P Somatic Mutation Status, Clinical Features, and Outcome. (13th August 2014) - Petrikkos, Loizos; Kyrtsonis, Marie-Christine; Roumelioti, Maria; Georgiou, George; Efthymiou, Anna; Tzenou, Tatiana; Panayiotidis, Panayiotis
Abstract : We performed IGH clonotypic sequence analysis in WM in order to determine whether a preferential IGH gene rearrangement was observed and to assess IGHV mutational status in blood and/or bone marrow samples from 36 WM patients. In addition we investigated the presence of MYD88 L265P somatic mutation. After IGH VDJ locus amplification, monoclonal VDJ rearranged fragments were sequenced and analyzed. MYD88 L265P mutation was detected by AS-PCR. The most frequent family usage was IGHV3 (74%); IGHV3-23 and IGHV3-74 segments were used in 26% and 17%, respectively. Somatic hypermutation was seen in 91% of cases. MYD88 L265P mutation was found in 65, 5% of patients and absent in the 3 unmutated. These findings did not correlate with clinical findings and outcome. Conclusion. IGH genes' repertoire differed in WM from those observed in other B-cell disorders with a recurrent IGHV3-23 and IGHV3-74 usage; monoclonal IGHV was mutated in most cases, and a high but not omnipresent prevalence of MYD88 L265P mutation was observed. In addition, the identification of 3 patients with unmutated IGHV gene segments, negative for the MYD88 L265P mutation, could support the hypothesis that an extra-germinal B-cell may represent the originating malignant cell in this minority of WM patients.